ANALISIS EFEKTIVITAS PELAKSANAAN BANTUAN TUNAI LANGSUNG (BLT) - Maya Widyana Dewi; Retno Puji Rahayu; Harum Melathi; LMS Kristiyanti (Jurnal Akuntansi dan Pajak, 2024)
The implementation of development programs is directed at improving the social welfare of the community so that they can live properly and be able to develop themselves, so that they can carry out their social functions. Poverty is one of the social inequalities that must be overcome when development is carried out. The Direct Cash Transfer (BLT) program is one of the government initiatives aimed at improving people's welfare. The objective to be achieved in this research is to determine the effectiveness of the implementation of the Direct Cash Transfer (BLT). In this study, researchers used descriptive data analysis techniques by collecting data by conducting interviews, observation, documentation and literature. The implementation of BLT distribution in Lumbungkerep village showed less than optimal results, namely in the indicators of targeting accuracy and benefit accuracy. The cause of the lack of targeting accuracy was poor coordination between levels of government regarding BLT recipient data. There were also allegations of nepotism that occurred in the selection process of BLT recipient candidates. Meanwhile, the cause of the non-optimized accuracy of benefits was that the BLT funds were not used in accordance with the purpose of the BLT funds themselves, but to cover other needs besides primary needs.